Pengaruh Manajemen Kelas Terhadap Hasil Belajar Siswa Kelas IV SDN Jrebeng Kidul - ., Nabila Maulidya; ., Ribut Prastiwi Sriwijayanti; ., Ryzca Siti Qomariyah (Jurnal Pendidikan, Sains Dan Teknologi, 2023)
The background of this research is that the classroom arrangements at SDN Jrebeng Kidul are not good enough, the classroom conditions and active interactions during the learning process are not optimal, so this research aims to find out the effect of class management to the learning outcomes of fourth grade students at SDN Jrebeng Kidul, Probolinggo City. This research is a quantitative research. The research design used was the One Group Pretest-Posttest Design, which only involved one class as the experimental class. Data collection methods used are questionnaires, learning achievement tests, observation and documentation. The results of inferential statistical analysis using the t test formula obtained a tCount of 8.02. With a frequency (dk) of 24-1 = 23, at a significant level of 5%, tTable = 2.068 is obtained because tCount > tTable at a significant level of 0.05, the null hypothesis (H0) is rejected and the working hypothesis (H1) is accepted, which means the implementation of management class influences the learning outcomes of fourth grade students at SDN Jrebeng Kidul.